John Brown's spirit: the abolitionist aesthetic of emancipatory martyrdom in early antilynching protest literature - Trodd, Zoe (Cambridge University Press, 2015)
Before his execution in 1859, the radical abolitionist John Brown wrote a series of prison letters that – along with his death itself – helped to cement the abolitionist aesthetic of emancipatory martyrdom. This article charts the adaptation of that aesthetic in antilynching protest literature during the decades that followed. It reveals Brown's own presence in antilynching speeches, sermons, articles, and fiction, and the endurance of the emancipatory martyr symbol that he helped to inaugurate. Between the 1880s and the 1920s, black and white writers imagined lynching's ritual violence as a crucifixion and drew upon the John Brown aesthetic of emancipatory martyrdom, including Frederick Douglass, Stephen Graham, James Weldon Johnson, Walter White, black Baptist ministers, and black educators and journalists. Fusing martyrdom and messianism, these antilynching writers made the black Christ of their texts an avenging liberatory angel. The testamentary body of this messianic martyr figure marks the nation for violent retribution. Turning the black Christ into a Brown-like prophetic sign of God's vengeful judgment, antilynching writers of the late nineteenth and early twentieth centuries warned of disaster, demanded a change of course, challenged white southern notions of redemption, and insisted that African Americans must reemancipate themselves and redeem the nation.